Dietary Tributyrin Administration Improves Intestinal Morphology and Selected Bacterial and Short-Chain Fatty Acid Profiles in Broilers Under an Isocaloric Feeding Regime - Hu, Qunbing; Yin, Fugui; Li, Baocheng; Guo, Yuming; Yin, Yulong (Frontiers in Microbiology, 2021)
The current study was conducted to investigate the effect of dietary tributyrin (TB) administration on the intestinal and growth performances in Arbor Acres (AA) broilers under an iso-caloric feeding regime. A total of 540 day-old healthy AA broilers were randomly assigned to 5 treatments with 12 replicates (pens) per treatment and 9 birds per pen for 42 d. The dietary treatments were basal diet (control) and basal diet with TB at the doses of 0.23 g/kg (TB1), 0.46 g/kg (TB2), 0.92 g/kg (TB3) and 1.84 g/kg (TB4), respectively. Particularly, to achieve the iso-caloric and cost-saving experimental diets, soybean oil was replaced by the TB product (Eucalorie®) with equivalent metabolic energy contents, and the formula were re-balanced with zeolite to get the sum of all the feed ingredients to 100%. On d 21 and 42, after weighing, the birds (one bird per replicate) whose body weight close to the replicate average were euthanized to investigate the effect of dietary TB on intestinal morphology, intestinal bacterial population and short chain fatty acid contents. The results revealed that dietary TB administration increased the average daily gain, gain/feed ratio and European broiler index (P < 0.05), as well as improved the intestinal morphology (P < 0.05) as indicated by higher villus height and the ratios of villus height/crypt depth in broilers. The incremental levels of TB increased the ileal Lactobacillus content (P = 0.05) and cecal Bacillus content (P = 0.02), respectively. Moreover, dietary TB administration also increased the contents of most of the selected short chain fatty acids in ileal and cecal digesta (P < 0.05). Collectively, dietary TB administration quadratically improved the growth performance, intestinal morphology, beneficial bacterial population and short chain fatty acid levels under the iso-caloric feeding regime, indicating better profit return potential in practical poultry operation.